RECENT TECHNOLOGICAL ADVANCEMENTS IN STROKE REHABILITATION: A SYSTEMATIC LITERATURE REVIEW ON INNOVATIONS, EFFECTIVENESS, AND IMPLEMENTATION IN PATIENT RECOVERY - Salsabila, Oessi (STIKES Syedza Saintika Padang, 2025)
Stroke remains a leading cause of long-term disability globally, significantly impacting motor, cognitive, and functional abilities. Traditional rehabilitation methods face challenges such as limited personalization, inconsistent engagement, and restricted accessibility, leading to the integration of advanced technologies. Recent innovations, including robotic-assisted therapies, virtual reality (VR), artificial intelligence (AI), and brain-computer interfaces (BCIs), address these limitations effectively. These technologies provide precise, scalable, and immersive rehabilitation interventions, improving recovery outcomes and adherence. This study aims to systematically review recent technological advancements in stroke rehabilitation, focusing on innovations, effectiveness, and implementation challenges. Employing the PRISMA 2020 framework, a comprehensive search was conducted across major databases, resulting in the selection of 16 relevant studies from an initial pool of 200 articles. Data from these studies were analyzed to assess the impact of advanced technologies on motor and cognitive recovery, and their integration into clinical settings. Findings indicate that robotic therapies and VR platforms outperform traditional methods in improving motor and cognitive functions. AI-driven solutions and BCIs facilitate personalized and adaptive rehabilitation, enhancing recovery trajectories for diverse patient populations. Significant barriers include high costs, technical complexity, and sociocultural factors affecting adoption. The lack of standardized protocols and limited long-term studies further hinder the widespread implementation of these technologies. Collaboration among researchers, clinicians, and policymakers is essential to address these issues. Recommendations include increasing access to affordable technologies, developing standardized training programs, and conducting large-scale, multicenter trials to validate long-term effectiveness. Closing these gaps ensures equitable access to advanced rehabilitation technologies and improves the quality of life for stroke survivors. This study underscores the transformative potential of technological innovations in stroke rehabilitation, providing valuable insights for future research and practice to optimize recovery outcomes and reduce the global burden of stroke-related disabilities.